Direct and contextual influence of team conflict on team resources, team work engagement and team performance - Costa, P. L.; Passos, A. M.; Bakker, A. B. (Negotiation and Conflict Management Research, 2015)
This article focuses on team conflict's direct influence on both team work engagement and team performance, as well as on its moderator role in the relationship between team resources and team work engagement and in the relationship between team work engagement and team performance. Data were collected from 82 research teams and team leaders, using electronic questionnaires; data on these teams' objective performance was also obtained. We found a direct influence of only task conflict on team work engagement. Moderation analysis revealed that relationship conflict weakens the relationship between team resources and team work engagement, whereas task conflict strengthens the relationship between team work engagement and team performance. Therefore, relationship conflict has a detrimental effect for the development of a positive emergent state of work engagement; on the contrary, discussing ideas positively influences the transformation of the team's level of engagement into objective performance.